2020
DOI: 10.3389/fmicb.2020.584947
|View full text |Cite
|
Sign up to set email alerts
|

Singularities of Pyogenic Streptococcal Biofilms – From Formation to Health Implication

Abstract: Biofilms are generally defined as communities of cells involved in a self-produced extracellular matrix adhered to a surface. In biofilms, the bacteria are less sensitive to host defense mechanisms and antimicrobial agents, due to multiple strategies, that involve modulation of gene expression, controlled metabolic rate, intercellular communication, composition, and 3D architecture of the extracellular matrix. These factors play a key role in streptococci pathogenesis, contributing to therapy failure and promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 262 publications
1
13
0
Order By: Relevance
“…In vivo colonization by the group of pyogenic streptococci requires a series of interactions between the pathogen and the host, involving differential gene expression in both ( Alves-Barroco et al., 2020 ). Our data revealed that in vivo , a similar number of sessile cells were recovered from SDSD isolates previously classified as weak and strong biofilm producers in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…In vivo colonization by the group of pyogenic streptococci requires a series of interactions between the pathogen and the host, involving differential gene expression in both ( Alves-Barroco et al., 2020 ). Our data revealed that in vivo , a similar number of sessile cells were recovered from SDSD isolates previously classified as weak and strong biofilm producers in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Streptococcus dysgalactiae harbors a great repertoire of adhesins that interact with the extracellular matrix of animal cells, including SfbI, GfbA, FbaA, FbaB, FBP54, and M-like proteins ( Alves-Barroco et al, 2020 ). Here, we found several adhesins ubiquitously and randomly distributed among S. dysgalactiae isolates, except the sdrE _2 gene that was found only in animal SDSE and human SDSD isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Pharyngeal infections, notably the ones caused by Streptococcus pyogenes, also produces the previously described structure of biofilm. And as well as in the oral cavity, in the pharynx bacteria in biofilms are less sensitive to host defense mechanisms and antimicrobial agents, due to multiple strategies, that involve modulation of gene expression, controlled metabolic rate, intercellular communication, composition, and 3D architecture of the extracellular matrix (55).…”
Section: Probiotics Use In Pharyngeal Infectionsmentioning
confidence: 99%